2012
DOI: 10.1021/nn3047633
|View full text |Cite
|
Sign up to set email alerts
|

Chiral-Selective CoSO4/SiO2 Catalyst for (9,8) Single-Walled Carbon Nanotube Growth

Abstract: Electronic and optical properties of single-walled carbon nanotubes (SWCNTs) correlate with their chiral structures. Many applications need chirally pure SWCNTs that current synthesis methods cannot produce. Here, we show a sulfate-promoted CoSO(4)/SiO(2) catalyst, which selectively grows large-diameter (9,8) nanotubes at 1.17 nm with 51.7% abundance among semiconducting tubes and 33.5% over all tube species. After reduction in H(2) at 540 °C, the catalyst containing 1 wt % Co has a carbon yield of 3.8 wt %, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
123
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 102 publications
(124 citation statements)
references
References 71 publications
1
123
0
Order By: Relevance
“…[34] In Figure 2(a), it is observed that nine major semiconducting species exist in the SDS suspended SWNTs. They are (6, 5), (7,5), (7,6), (8,4), (8,6), (8,7), (9, 4), (9, 5) and (10, 2) which are marked with orange borders in Figure 2(c). While nine species can also be observed in Figure 2(b) which are semiconducting enriched fractions after AGE/w-PFO.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…[34] In Figure 2(a), it is observed that nine major semiconducting species exist in the SDS suspended SWNTs. They are (6, 5), (7,5), (7,6), (8,4), (8,6), (8,7), (9, 4), (9, 5) and (10, 2) which are marked with orange borders in Figure 2(c). While nine species can also be observed in Figure 2(b) which are semiconducting enriched fractions after AGE/w-PFO.…”
Section: Resultsmentioning
confidence: 99%
“…While nine species can also be observed in Figure 2(b) which are semiconducting enriched fractions after AGE/w-PFO. They are (7,5), (7,6), (8,4), (8,6), (8,7), (9, 4), (9, 5), (10,2), and (10, 3) which are marked with green dots of different darkness in Figure 2(c), according to calibrated PL peak intensity. In the graphene sheet map, Figure 2(c), the suspension preferences of pristine SWNTs and semiconducting enriched SWNTs by AGE/w-PFO are summarized.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations